Flujo de polen entre hibridos tropicales de maiz de diferente color de endospermo - Guzman H, M.=700 1 San Vicente G, F.; Diaz M, D.
(Es, En)
Ilus., 21 ref.
Keywords: MAIZ; HIBRIDOS; TRANSGENICOS; VIENTO; POLEN; VENEZUELA; BIOAGRO